ANALYSIS OF WAITING TIME AND HUMAN RESOURCES COMPETENCE TOWARDS CUSTOMER SATISFACTION AT MAYANG COMMUNITY HEALTH CENTER (A LITERATURE STUDY OF HUMAN RESOURCES MANAGEMENT) - Supriyanto, Hamid Dwi; Toni Herlambang; Haris Hermawan (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This article reviews the effect of waiting time, friendliness of officers, and competence of officers on customer satisfaction at Mayang Health Center. Method: The method of writing this scientific article is with qualitative methods and literature studies. Results: The results of this literature review article are as follows: (1) Waiting time has a positive and significant effect on customer satisfaction at Mayang Health Center. (2) Competence of officers has a positive and significant effect on customer satisfaction at Mayang Health Center. Novelty: This study provides insights into the relationship between waiting time, officer competence, and customer satisfaction at Mayang Health Center, contributing to the understanding of service quality in healthcare facilities.